2000
DOI: 10.1046/j.1525-1594.2000.06587.x
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Assisted Cardiopulmonary Bypass in Minimally Invasive Cardiac Surgery: Its Feasibility and Effects on Hemolysis

Abstract: The present study describes a cardiopulmonary bypass (CPB) technique that incorporates vacuum assisted venous drainage and arterial return using a centrifugal pump in minimally invasive cardiac surgery (MICS). The technique was performed on 40 patients scheduled to undergo MICS. The proposed CPB technique enables a good operative field to be obtained even through a limited incision through the use of peripheral cannulation using small cannulae. Vacuum pressure was applied to the venous reservoir (-43 +/- 14 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…These include use of cell salvage (which in our study was not associated with increased risk of infection), use of small priming volume cardiopulmonary bypass circuits, minimizing hemodilution by crystalloid fluids, use of vacuum-assisted venous return (36, 37) with rapid autologous priming (38), increase in hematocrit by modified ultrafiltration (39), elevation of preoperative hematocrit in elective cases by iron and B-complex vitamin administration, and, possibly, the selective use of erythropoetin, although not approved by the FDA for this indication (40, 41). In addition, attention to intraoperative hemostasis, establishment of protocols for transfusion and reoperation for bleeding, use of anti-fibrinolytics, and a tolerance for mild-to-moderate anemia are reasonable means to reduce use of a scarce resource (35).…”
Section: Commentmentioning
confidence: 80%
“…These include use of cell salvage (which in our study was not associated with increased risk of infection), use of small priming volume cardiopulmonary bypass circuits, minimizing hemodilution by crystalloid fluids, use of vacuum-assisted venous return (36, 37) with rapid autologous priming (38), increase in hematocrit by modified ultrafiltration (39), elevation of preoperative hematocrit in elective cases by iron and B-complex vitamin administration, and, possibly, the selective use of erythropoetin, although not approved by the FDA for this indication (40, 41). In addition, attention to intraoperative hemostasis, establishment of protocols for transfusion and reoperation for bleeding, use of anti-fibrinolytics, and a tolerance for mild-to-moderate anemia are reasonable means to reduce use of a scarce resource (35).…”
Section: Commentmentioning
confidence: 80%
“…Thanks to technological advancements that now allow for the development of minimally invasive cardiac surgery, where the technique of VAVD has been essential safely and effectively [7][8][9][10], is also increasing the number of studies on the use of this technique in cardiac surgery of access and traditional cannulation. In this sense, these authors cite several benefits gained by the substitution of conventional drainage, which is based on sinfonagem and gravity drainage by using the active vacuum [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al 16 showed that this approach does not appreciably increase haemolysis compared with traditional CPB.…”
Section: Flow and Venous Drainagementioning
confidence: 99%